Banking crises and "Japanization": Origins and implications - Masahiro Kawai; Peter Morgan (Asian Development Bank Institute (ADBI), 2013)
Japan's "two lost decades" perhaps represent an extreme example of a weak recovery from a financial crisis, and are now referred to as "Japanization." More recently, widespread stagnation in advanced economies in the wake of the global financial crisis led to fears that Japanization might spread to other countries. This study examines the dimensions of Japanization - including low trend growth, debt deleveraging, deflation, and massive increases in government debt - and analyzes their possible causes - including inadequate macroeconomic policy responses, delayed banking sector restructuring, inadequate corporate investment, loss of industrial competitiveness, a slowdown in total factor productivity (TFP) growth due to excessive regulation and economic rigidities, and an aging society.
Keywords: E20; E31; E51; F31; G01; 330; economic growth; total factor productivity; inflation; demographics; credit growth; banking crises; Bankenkrise; Makroökonomischer Einfluss; Wirtschaftliche Anpassung; Japan